التجارة بين بلاد النوبة ومصر القديمة (2900 ـ 1085) ق.م - مشانة، أيمن (جامعة الوادي university of Eloued, 2020)
الملخص: تتمثل الدراسة في محاولة جادة لدراسة تاريخ تطور العلاقة المتبادلة بين مصر القديمة أقرب جيرانها من جهة الجنوب الإفريقي أي بلاد النوبة، وكيف أثرت التجارة بين بلاد النوبة ومصر القديمةفي التطور الحضاري والاقتصادي للمنطقة والذي عرفت من خلاله الاقتصاديات النوببية تطورا في الناحية الصناعية والتجارية ، كما هي محاولة لبحث أهمية الضفة الجنوبية للقارة الإفريقية وخيراتها ومواردها الاقتصادية الضخمة والتي ساهمت بشكل كبير في بناء مجد مصر القديمة وحضارتها. Résumé : The study centers on a serious attempt to study the history of the development of the reciprocal relationship between ancient Egypt and its closest neighbors from the southern African side, that is, the ancient Nubian countries, and how the trade between them affected the civilizational and economic development of the region, through which the economies have known development in the industrial and commercial aspect, as it is an attempt to examine the importance of The southern bank of the African continent and its wealth and huge economic resources, which greatly contributed to building the glory and civilization of ancient Egypt
مذكرة ماستر تاريخ تخصص الحضارات القديمة
Keywords: مصر القديمة، بلاد النوبة; Égypte ancienne, Nubie; Ancient Egypt, Nubia